Características clínico-epidemiológicas y manejo de las malformaciones arteriovenosas cerebrales en el Servicio de Neurocirugía del Instituto Nacional de Salud del Niño San Borja, 2015-2017 - Cordero Campos, Alem (2021)
Objective: To describe the clinical–epidemiological characteristics and management of cerebral arteriovenous malformations (AVM) in patients treated at the Instituto Nacional de Salud del Niño San Borja (INSN–SB). Materials and methods: A retrospective and descriptive study conducted in patients with AVM treated at the INSN–SB between 2015 and 2017. Data was processed and analyzed using IBM SPSS Statistics statistical software version 22. The qualitative variables were expressed in absolute and relative frequencies. Results: Forty-one (41) AVM cases were identified, being more frequent in the age group between 6 and 12 years (56.10 %) and in females (65.90 %). Ruptured AVM occurred in 80.49 % of the patients and 92.70 % claimed that headache was the most frequent clinical manifestation. The anatomical areas with the highest occurrence of AVM were the frontal lobe (36.60 %) and the left cerebral hemisphere (51.20 %). Grade III AVM was the most common one (43.90 %) according to the Spetzler-Martin grading scale. The most frequently used treatment was embolization (39 %) and mortality accounted for 2.40 %. Conclusions: AVM most frequently occurred in females and patients between 6 and 12 years old. A little more than half of the patients had a ruptured AVM. Headache was the predominant symptom of this disease. Most patients showed grade III AVM according to the Spetzler-Martin grading scale. Embolization was the most frequently used surgical method and the mortality rate was low.